The Perspectives of Medicine Students and Academic Members in Tabriz University of Medical Sciences about the Required Infrastructures for Implementation of Proposed Peer Assisted Learning (PAL) System - Mahasti Alizadeh; Mahasti Alizadeh; Farid Gharibi; Mohammad Asghari Jafar Abadi; Nima Esmaeilinasab; Zahra Bostani; Faraz Zarghami (Kerman University of Medical Sciences, 2012)
Background & Objectives: One of the remarkable innovations in enhancement of human forces ability especially in universities is utilization of experiments and capacities of students in the higher years of a course of study in the training of those in lower years in an updated system named Peer Assisted Learning (PAL) Current study aims to survey the perspectives of academic members and students in the Faculty of Medicine Tabriz University of Medical Sciences about the required infrastructures for implementation of Peer Assisted Learning proposed by the research group Methods: Following a vast literature review and interviews with experienced educational experts the researchers designed a questionnaire about the required infrastructures for the implementation of peer assisted learning Content validity of the questionnaire was confirmed by obtaining the opinions of 10 experts and reliability was confirmed through a pilot study A total of 289 medical students and academic members participated in the study Data were analyzed by SPSS 16 Results : According to the obtained results implementation of this system requires administration of abundant prerequisites and infrastructures that can be categorized into 5 topics of "selecting appropriate educators" "preparing the educators for acting properly" "creating adequate and effective motivation in educators" "modifying educational frames and rules for administration of this system" and "planning and supervision to achieve a successful administration of the proposed system" Conclusion: Most participants were in agreement with the proposed infrastructures and the obtained results were similar to those found in previous studies and similar systems Executive leaders in this field should notice that successful implementation of the proposed system requires numerous infrastructures